Title Application of Brain Gym in Fine Motor Developmentof Early Children (Study at Lembaga Pendidikan Anak Hebat Indonesia Unit 1418 Desa Plunturan Ponorogo) - Niswatul Imsiyah; Sylva Alkornia; Fiki Rona Hamamah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
This study aims to describe the application of brain age in the subtle development of early childhood in Indonesia's great children's educational institution unit 1418 Plunturan Ponorogo Village. This research is a type of qualitative descriptive research. Located at the AHE Institution Unit 1418 Plunturan Village, Pulung District, Ponorogo Regency using the Purposive Area technique. informants used purposive sampling technique. Data collection techniques using interviews, observation and documentation. The technique of checking the validity of the data uses observation, persistence and triangulation of sources, techniques and time. Data analysis went through four stages, namely data collection, data reduction, data presentation, and data verification. The results of the study stated that the number 8 sleep brain exercise applied at the AHE institution really helped early childhood in learning motor skills, especially in reading and writing. through brain exercises that are applied to institutions can help develop children's development to suit the stages that are passed by children so that they are able to achieve the level of mastery of skills spontaneously.